The design of a switched capacitor DC-DC converter for BMS - Li, Pingyuan (Nanyang Technological University, 2023)
This report describes the design of a switch capacitor DC-DC converter for a battery management system (BMS). The converter is designed to regulate the voltage of the battery and provide a stable output voltage to the load. The SC-DC converter uses a switched capacitor (SC) topology, which offers advantages such as high efficiency, low EMI, and low component count. The converter is controlled using a pulse-width modulation (PWM) technique, which adjusts the duty cycle of the switching signals to regulate the output voltage. The design is optimized for a wide range of input from 1V to 3.6V and able to drive a load up from 1uA to1mA with a ripple voltage less than 0.1V.